Investment specific technological progress and structural change - Araujo, Ricardo Silva Azevedo (2010)
In this paper we introduce investment specific technical progress into Pasinetti's model of structural change. Our aim is to assess the effects of embodied technical progress on economic growth and macroeconomic variables. Our findings suggest that despite the fact that this type of technical progress increases the productivity of capital, it has negative effects on conditions that promote full employment.